Knowledge Engineering: Practice and Patterns - Gangemi, Aldo (Springer, 2017)
This book constitutes the refereed proceedings of the 16th International Conference on Knowledge Engineering and Knowledge Management, EKAW 2008, held in Acitrezza, Sicily, Italy, in September/October 2008.